How to keep well in wartime - Great Britain. Ministry of Health ; Central Council for Health Education (Great Britain); Clegg, Hugh Anthony, 1900- (London : His Majesty's Stationery Office, 1943)
1943 1943 1940s 28 pages : illustrations BE MODERATE IN ALL THINGS finally broken down to carbon dioxide and water. Three-quarters of the brain is water. As has already been said, water is being lost at varying rates through the skin and the lungs, in the urine, and in the faeces. Water plays a vital part in all the chemical and physical changes in the body. Yet some people think it is just stuff to wash in. Water is meant to be drunk. In fact you must drink it, or you would die of thirst. You should take some three pints a day. Most people like their water coloured rather than plain, even if the colour is only that of weak tea or bad coffee. Some people still like a glass of beer, though they will tell you that nowadays it is little better than coloured water. You can drink too much tea, too much coffee, too much beer. It can't be said that any of them do you any good. Too much always does harm. Few people drink enough water. So see that you get enough of it yourself. 6. Be Moderate in All Things Drinks like tea, coffee, beer, gin, whisky, rum have their attractions, of course. A cup of tea often "bucks you up". But alcohol may act as a poison; it certainly does when an overdose is taken. A drunk person is a person poisoned with alcohol. The alcohol called "hooch" is such a strong poison that it blinds and even kills people. To take a glass of beer with a friend is a pleasant social custom. But don't delude yourself that beer does you good, because it doesn't. Are We Smoking too Much? Another overworked social custom is smoking. The consumption of tobacco went up by leaps and bounds at the beginning of the war. Tobacco may soothe the nerves, but it may also spoil the appetite and irritate the mouth, throat, and lungs. It can upset the digestion, and interfere with mental and physical efficiency. Two years before the war, in 1937, this country spent £150,000,000 on tobacco. There appear to be social virtues in smoking. It has certainly become a social habit, and in many cases a bad habit. Most people can quote examples of hale and hearty old men of 80 who have smoked all their lives without harm. And there is Mr. Churchill with his cigars. But these are exceptional men. For the ordinary man and woman good health will not be theirs unless they smoke in strict moderation. King James I said of smoking that it is "a custom loathsome to the eye, hateful to the nose, harmful to the brain, dangerous to the lungs, and in the black stinking fume thereof nearest resembling the horrible stygian smoke of the bottomless pit ". This was, of course, laying it on a bit thick. Not a Cure for Nerves. There is no doubt that smoking too much 13 420/BS/7/16/18